Isolated Persistent Left Superior Vena Cava Revealed by an Associated Asthma - I. Bachouch; N. Belloumi; M. Attia; F. Chermiti Ben Abdallah; S. Hantous Zannad; S. Fenniche (Case Reports in Vascular Medicine)
Background. Persistent left superior vena cava (PLSVC) is a rare anomaly of the thoracic venous system. Case Report. We present a case of a patient with isolated asymptomatic PLSVC, who was diagnosed because of dyspnea revealing an associated asthma. An 18-year-old male patient complained of paroxystic sibilant dyspnea. He did not have any anomaly in physical examination. The chest X-ray revealed cardiomegaly with a widening of lower mediastinum. The electrocardiogram does not show any anomaly. Echocardiography showed the PLSVC. The thoracic contrast computed tomography of the chest showed ecstasies of the right cardiac cavities and a double superior vena cava. The patient did not have similar family cases. Respiratory functional explorations led to the diagnosis of an associated asthma. Currently, he is followed up periodically. Asthma was improved with inhaled corticosteroid treatment. Conclusion. PLSVC is rare but can have important clinical implications. Associated severe cardiac malformations must be systematically sought.